Peer Connectedness and Pre‐Existing Social Reward Processing Predicts U.S. Adolescent Girls' Suicidal Ideation During COVID‐19. (26th August 2021) - Hutchinson, Emily A.; Sequeira, Stefanie L.; Silk, Jennifer S.; Jones, Neil P.; Oppenheimer, Caroline; Scott, Lori; Ladouceur, Cecile D.
Abstract : There is major concern about the impact of the COVID‐19 pandemic on adolescent suicidal ideation (SI) and peer relationships. We investigated (1) rates of SI and (2) the extent to which peer connectedness and pre‐existing neural activation to social reward predicted SI during the initial stay‐at‐home orders of the pandemic (April–May 2020) in a longitudinal sample of adolescent girls ( N  = 93; M age  = 15.06; 69% White non‐Hispanic). Daily diary and fMRI methods were used to assess peer connectedness and neural activation to social reward, respectively. Nearly 40% of girls endorsed SI during the initial stay‐at‐home orders. Greater peer connectedness and neural responsivity to anticipated social reward were associated with a reduced odds of SI during the pandemic among girls.